A Generalized Framework for the Alternate Load Path Redundancy Analysis of Steel Truss Bridges Subjected to Sudden Member Loss Scenarios - Huihui Li; Lian Shen; Shuwen Deng (Buildings, 2022)
Owing to their distinct features, such as structural simplicity and excellent load-carrying capacity, steel truss bridges are widely applied as critical transportation networks. However, many previously designed steel truss bridges that are located in harsh environmental conditions are facing severe challenges of overloading and aging or deteriorating critical structural members due to increasing traffic load and corrosion problems (i.e., chloride-induced corrosion). As a consequence, these overloaded and deteriorated critical members may initialize localized damage (e.g., sudden member failure scenarios) and then trigger a disproportionate collapse (i.e., progressive collapse) of steel truss bridges. To this end, to protect the steel truss bridges from progressive collapse resulting from locally induced damages (e.g., sudden removal of a critical member), this paper proposed a generalized framework to identify the critical members and to qualify the alternate load path (ALP) redundancy of steel truss bridges subjected to sudden member loss of a critical member. Demand-to-capacity ratio (DCR) for linear elastic analysis and strain ratio (SR) for nonlinear dynamic analysis were employed as the design metrics and performance indicators to qualify the ALP redundancy of steel truss bridges. Effectiveness of the proposed framework in qualifying the ALP redundancy of steel truss bridges was demonstrated through the I-35W truss bridge under sudden member removal (MR) analyses. Results obtained from this study may provide beneficial information and could serve as good references for the protection of steel truss bridges that are vulnerable to sudden member loss scenarios.